Anti-adhesion low-temperature-resistant material as well as preparation method and application thereof

By introducing fluorine-containing POSS and polysiloxane into medical polymer materials and adopting specific preparation processes, the problem of material flexibility decreases under low temperature conditions is solved, and efficient anti-adhesion and low temperature resistance is achieved, and it is suitable for medical catheters and other products.

CN119529447AActive Publication Date: 2025-02-28HENAN TUOREN MEDICAL TECH CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411860980.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The flexibility of existing medical polymer materials decreases under low temperature conditions, which is prone to cracking and fracture problems, and it is difficult to effectively prevent blood clots and bacteria from growing.

Method used

The combination of polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, cross-linking additive MBS, wax powder, polyethylene oxide and anionic surfactant was prepared by a high-mixer stirring, heating stirring, melt kneading and extrusion granulation.

Benefits of technology

The material can reach more than 40% in break at -10℃, and can reach more than 300% in break at 25℃, with glass transition temperature below -21℃, low dynamic friction coefficient, and increased water contact angle to 140°. It has excellent low temperature resistance and anti-adhesion properties, and is suitable for use in medical catheters and other products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193195080000181
    Figure BDA0005193195080000181
  • Figure BDA0005193195080000191
    Figure BDA0005193195080000191
  • Figure BDA0005193195080000201
    Figure BDA0005193195080000201
Patent Text Reader

Abstract

The invention provides an anti-adhesion and low-temperature-resistant material and a preparation method thereof. The high-temperature-resistant polyvinyl chloride material is prepared from the following raw materials in parts by weight: 100 parts of polyvinyl chloride resin, 1 to 5 parts of fluorine-containing octavinyl polyhedral oligomeric silsesquioxane (fluorine-containing POSS), 3 to 8 parts of polysiloxane, 5 to 10 parts of a composite heat stabilizer, 5 to 10 parts of epoxidized soybean oil, 30 to 70 parts of a plasticizer, 1 to 5 parts of a cross-linking aid MBS, 0.5 to 1.5 parts of polyoxyethylene, 0.5 to 1.5 parts of polyoxyethylene, 0.5 to 5 parts of wax powder and 0.1 to 0.5 part of an anionic surfactant. The elongation at break of the anti-adhesion low-temperature-resistant material at-10 DEG C can reach 40% or above, the elongation at break of the anti-adhesion low-temperature-resistant material at 25 DEG C can reach 300% or above, the glass-transition temperature is-21 DEG C or below, the dynamic friction coefficient is as low as 0.33, and the water contact angle is increased to 140 degrees. Meanwhile, the invention also provides a preparation method and an application method of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a medical polymer material, in particular to an anti-adhesion and low-temperature resistant material and a preparation method and application thereof. Background Art

[0002] Polyvinyl chloride (PVC) is widely used in medical devices that come into contact with human blood and tissues due to its excellent mechanical properties, chemical corrosion resistance, and wear resistance. For example, disposable medical supplies such as hemodialysis systems, extracorporeal circulation systems, and urinary catheters bring many conveniences to treatment and care, and can prevent cross infection. However, when used as a medical catheter, the surface polarity of PVC material is large, and the surface is easily adsorbed with proteins, bacteria, and some biological cells, causing wound infection, inflammation, and thrombosis. In particular, when blood contacts the surface of medical devices, plasma proteins will quickly adsorb to the surface of the material and bind to the glycoprotein receptors of platelets, leading to platelet activation, coagulation cross-linking, and complement activation, and eventually forming thrombi. When nutrient solution or blood remains on the surface of the catheter, it will cause a large number of bacteria to grow, and coagulation or residual fluid will cause valve adhesion and catheter obstruction. Therefore, biomedical materials are usually faced with the test of coagulation problems.

[0003] In response to this problem, a large number of studies on the modification of medical polymer materials have been carried out at home and abroad, such as: blending, copolymerization modification of PVC resin, surface modification of PVC materials or products, etc. However, these medical polymer materials all have some defects.

[0004] For example, Chinese patent CN105061928A discloses a modified PVC granular material for hemodialysis tubing, which uses orthophthalic plasticizer and lead salt stabilizer, and has certain safety risks; Chinese patent CN116061354A discloses a medical catheter and a preparation method thereof, which uses laser or chemical etching to process micron-level and nano-level alternating textures on the mold surface, and obtains the medical catheter by injection molding; the micron-level and nano-level alternating physical textures on the inner and outer surfaces of the medical catheter make it hydrophobic, antibacterial and anticoagulant, but the performance of the material itself has not been improved, and the biocompatibility needs to be improved; Chinese patent CN115746475A discloses an anti-adhesion polymer material and a preparation method thereof, which obtains an anti-adhesion polymer material by blending and granulating an acrylate-based amphiphilic copolymer and a high molecular polymer in proportion, but does not take into account the low-temperature resistance of the material. At low temperatures, the flexibility of the material is greatly reduced, and the risk of cracking and breaking of the product is relatively high. If this situation occurs during the use of the patient, it will pose a threat to the patient's life safety.

[0005] In order to solve the above problems, people have been seeking an ideal technical solution. Summary of the invention

[0006] The purpose of the present invention is to provide an anti-adhesion low-temperature resistant material and a preparation method and application thereof in view of the deficiencies in the prior art.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] An anti-adhesion and low-temperature resistant material comprises, by weight, 100 parts of polyvinyl chloride resin, 1-5 parts of fluorinated octavinyl cage-type polysilsesquioxane (fluorinated POSS), 3-8 parts of polysiloxane, 5-10 parts of composite heat stabilizer, 5-10 parts of epoxy soybean oil, 30-70 parts of plasticizer, 1-5 parts of crosslinking aid MBS, 0.5-1.5 parts of polyethylene oxide, 0.5-5 parts of wax powder and 0.1-0.5 parts of anionic surfactant.

[0009] The raw materials of fluorine-containing octavinyl cage-type polysilsesquioxane include, by weight, 10 parts of cage-type polysilsesquioxane (POSS), 2-15 parts of 1H,1H,2H,2H-perfluorodecanethiol, 0.1-1 parts of 2,2-dimethoxyphenylacetophenone and 100-150 parts of dichloromethane;

[0010] The preparation method of fluorine-containing octavinyl cage-type polysilsesquioxane comprises the following steps:

[0011] The cage-type polysilsesquioxane, 1H,1H,2H,2H-perfluorodecanethiol and 2,2-dimethoxyphenylacetophenone are dissolved in a dichloromethane solution; the mixture is reacted for 10 to 20 minutes under 300 to 500W ultraviolet light irradiation, and a white precipitate is obtained by centrifugation; and the fluorinated octavinyl cage-type polysilsesquioxane is obtained after washing and drying.

[0012] The average degree of polymerization of polyvinyl chloride resin is 1000-1800; the number average molecular weight of polysiloxane is 1000-15000; the number average molecular weight of polyethylene oxide is 1×10 5 ~1×10 6 .

[0013] The composite heat stabilizer comprises a main stabilizer and an auxiliary stabilizer in a mass ratio of (2-4):1, wherein the main stabilizer is stabilizer 1010 and stabilizer 168 in a mass ratio of 2:1; and the auxiliary stabilizer is phosphite.

[0014] The plasticizer is one of diisooctyl cyclohexane 1,2-dicarboxylate, diisononyl cyclohexane 1,2-dicarboxylate, and tributyl acetyl citrate, or a combination of at least two of them.

[0015] The wax powder is polyamide wax and maleic anhydride grafted PE wax in a mass ratio of 1:(1-2); the anionic surfactant is one of sodium secondary alkyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and polystyrene sulfonic acid in a mass ratio of 1:(2-3).

[0016] A method for preparing an anti-adhesion and low-temperature resistant material comprises the following steps:

[0017] Add polyvinyl chloride resin, fluorinated octavinyl cage polysilsesquioxane, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant into a high-speed mixer, and stir evenly at 500-800 rpm to obtain a mixture a;

[0018] Raise the temperature to 40-50°C, add plasticizer to mixture a, continue stirring at 800-1100 rpm and raise the temperature to 80-100°C to obtain mixture b;

[0019] The mixture is cooled to 20-30°C, melt-kneaded at 80-170°C, plasticized, extruded, and finally granulated to obtain an anti-adhesion and low-temperature resistant material.

[0020] A single-screw or twin-screw extruder is used for melt kneading at 80-170°C, a screw speed of 40-100 rpm, a screw feed section temperature of 80-120°C, a plasticizing and melting section temperature of 130-150°C, and a die discharge section temperature of 150-170°C.

[0021] A method for applying the anti-adhesion and low-temperature resistant material. The anti-adhesion and low-temperature resistant material is used for continuous renal replacement therapy circuits, extracorporeal membrane oxygenation circuits, extracorporeal circulation circuits, vascular access for dialysis indwelling needles, and vascular access for disposable arteriovenous puncture devices.

[0022] The anti-adhesion and low-temperature resistant material is extruded and formed by a pipe extruder; the temperature of the heating area of ​​the pipe extruder is 145°C to 175°C, the temperature of the mold is 130°C to 150°C, and the temperature of the cooling water tank is 40°C to 60°C.

[0023] The present invention has outstanding substantive features and significant progress compared to the prior art. Specifically, the present invention provides an anti-adhesion and low-temperature resistant material, the elongation at break at -10°C can reach more than 40%, the elongation at break at 25°C can reach more than 300%, the glass transition temperature is below -21°C, the dynamic friction coefficient is as low as 0.33, the water contact angle is increased to 140°, and it has excellent low-temperature resistance and anti-adhesion properties, and is suitable for use in medical products such as continuous renal replacement therapy circuits, extracorporeal membrane oxygenation circuits, extracorporeal circulation circuits, vascular access for dialysis indwelling needles, and vascular access for disposable arteriovenous puncture devices. At the same time, the present invention also provides a preparation method for the anti-adhesion and low-temperature resistant material, which is simple, easy to operate, and suitable for industrial promotion. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described in detail below through specific implementation methods.

[0025] Example 1

[0026] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 3 parts of fluorine-containing POSS, 5 parts of polysiloxane, 6 parts of composite heat stabilizer, 8 parts of epoxy soybean oil, 50 parts of cyclohexane 1,2-diisononyl dicarboxylate, 3 parts of cross-linking aid MBS, 0.5 parts of polyethylene oxide, 2 parts of wax powder and 0.3 parts of anionic surfactant.

[0027] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.5 parts of 2,2-dimethoxyphenyl acetophenone, 5 parts of 1H,1H,2H,2H-perfluorodecanethiol and 125 parts of dichloromethane in parts by mass. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 3:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:1.5; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:2; the crosslinking aid is a core-shell structured terpolymer of methyl methacrylate, butadiene and styrene (MBS crosslinking aids PA40 and PA60 of Japan Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1000; the number average molecular weight of polysiloxane is 10000; the number average molecular weight of polyethylene oxide is 1×10 5 .

[0028] The fluorine-containing POSS is prepared by the following method: POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol are dissolved in dichloromethane to prepare a solution, stirred evenly and reacted under 300W ultraviolet light for 12 minutes; the obtained white precipitate is centrifuged; the white solid precipitate is filtered out with a negative pressure filtration device, washed with dichloromethane, and filtered repeatedly with a negative pressure filtration device three times, and the filtered solid powder is vacuum dried at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0029] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0030] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-diisononyl dicarboxylate (DINCH) is added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0031] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 50℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0032] Example 2

[0033] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 5 parts of fluorine-containing POSS, 8 parts of polysiloxane, 6 parts of composite heat stabilizer, 7 parts of epoxy soybean oil, 60 parts of cyclohexane 1,2-diisononyl dicarboxylate, 4 parts of cross-linking aid MBS, 1.5 parts of polyethylene oxide, 3 parts of wax powder and 0.3 parts of anionic surfactant.

[0034] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.13 parts of 2,2-dimethoxyphenyl acetophenone, 15 parts of 1H,1H,2H,2H-perfluorodecanethiol and 134 parts of dichloromethane in terms of mass fractions. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer in a mass ratio of 2:1, the main stabilizer is stabilizer 1010 and stabilizer 168 in a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax in a mass ratio of 1:1; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid in a mass ratio of 1:3; the crosslinking aid is a terpolymer of methyl methacrylate, butadiene and styrene with a core-shell structure (MBS crosslinking aids PA40 and PA60 of Japan Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1800; the number average molecular weight of polysiloxane is 15000; the number average molecular weight of polyethylene oxide is 1×10 6 .

[0035] The fluorine-containing POSS is prepared by the following method: POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol are dissolved in dichloromethane to prepare a solution, stirred evenly and reacted under 300W ultraviolet light for 15 minutes; the obtained white precipitate is centrifuged; the white solid precipitate is filtered out with a negative pressure suction filtration device, washed with dichloromethane, and filtered repeatedly with a negative pressure suction filtration device three times, and the filtered solid powder is vacuum dried at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0036] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0037] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-diisononyl dicarboxylate (DINCH) is added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0038] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 45℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0039] Example 3

[0040] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 1 part of fluorine-containing POSS, 3 parts of polysiloxane, 5 parts of composite thermal stabilizer, 6 parts of epoxy soybean oil, 40 parts of acetyl tributyl citrate (ATBC), 1 part of cross-linking aid MBS, 0.8 parts of polyethylene oxide, 0.5 parts of wax powder and 0.1 parts of anionic surfactant.

[0041] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.71 parts of 2,2-dimethoxyphenyl acetophenone, 9 parts of 1H,1H,2H,2H-perfluorodecanethiol and 125 parts of dichloromethane in terms of mass fractions. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 4:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:2; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:2.5; the crosslinking aid is a terpolymer of methyl methacrylate, butadiene and styrene with a core-shell structure (MBS crosslinking aids PA40 and PA60 of Japan Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1500; the number average molecular weight of polysiloxane is 12000; the number average molecular weight of polyethylene oxide is 1×10 6 .

[0042] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 380W ultraviolet light for 13 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0043] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0044] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800rpm to obtain a mixture a; the temperature rises to 45°C, acetyl tributyl citrate (ATBC) is added to the mixture a, and the mixture is continuously stirred at 800-1100rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried to obtain an anti-adhesion and low-temperature resistant material. Among them, the main screw speed is 40-100rmp, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die discharge section is 150-170°C. The material is plasticized by extruder and granulated by air cooling.

[0045] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 60℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0046] Example 4

[0047] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 3.5 parts of fluorine-containing POSS, 5 parts of polysiloxane, 5 parts of composite heat stabilizer, 7 parts of epoxy soybean oil, 25 parts of cyclohexane 1,2-diisononyl dicarboxylate (DINCH), 20 parts of cyclohexane 1,2-diethylhexyl dicarboxylate (DEHCH), 2 parts of cross-linking aid MBS, 1.1 parts of polyethylene oxide, 2.5 parts of wax powder and 0.2 parts of anionic surfactant.

[0048] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.45 parts of 2,2-dimethoxyphenyl acetophenone, 7.8 parts of 1H,1H,2H,2H-perfluorodecanethiol and 137 parts of dichloromethane in terms of mass fractions. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer in a mass ratio of 2:1, the main stabilizer is stabilizer 1010 and stabilizer 168 in a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax in a mass ratio of 1:1.5; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid in a mass ratio of 1:3; the crosslinking aid is a core-shell structured terpolymer of methyl methacrylate, butadiene and styrene (MBS crosslinking aids PA40 and PA60 of Japan's Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1200; the number average molecular weight of polysiloxane is 12000; the number average molecular weight of polyethylene oxide is 5×10 5 .

[0049] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 330W ultraviolet light for 11 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0050] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0051] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dicarboxylic acid diisooctyl ester (DEHCH) and cyclohexane 1,2-dicarboxylic acid diisononyl ester (DINCH) are added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0052] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 45℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0053] Example 5

[0054] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 2 parts of fluorine-containing POSS, 4 parts of polysiloxane, 6 parts of composite heat stabilizer, 7 parts of epoxy soybean oil, 25 parts of cyclohexane 1,2-diisononyl dicarboxylate (DINCH), 35 parts of acetyl tributyl citrate (ATBC), 3.5 parts of cross-linking aid MBS, 1 part of polyethylene oxide, 1 part of wax powder and 0.2 parts of anionic surfactant.

[0055] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.33 parts of 2,2-dimethoxyphenyl acetophenone, 3 parts of 1H,1H,2H,2H-perfluorodecanethiol and 100 parts of dichloromethane in parts by mass. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 3:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:1; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:3; the crosslinking aid is a terpolymer of methyl methacrylate, butadiene and styrene with a core-shell structure (MBS crosslinking aids PA40 and PA60 of Japan Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1600; the number average molecular weight of polysiloxane is 12000; the number average molecular weight of polyethylene oxide is 1×10 6 .

[0056] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 300W ultraviolet light for 10 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0057] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0058] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir evenly at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dicarboxylic acid diisononyl ester (DINCH) and acetyl citrate tributyl ester (ATBC) are added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0059] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 45℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0060] Example 6

[0061] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 2.5 parts of fluorine-containing POSS, 6 parts of polysiloxane, 8 parts of composite heat stabilizer, 9 parts of epoxy soybean oil, 30 parts of cyclohexane 1,2-diethylhexyl dicarboxylate (DEHCH), 35 parts of acetyl tributyl citrate (ATBC), 5 parts of cross-linking aid MBS, 1.2 parts of polyethylene oxide, 4 parts of wax powder and 0.4 parts of anionic surfactant.

[0062] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.53 parts of 2,2-dimethoxyphenyl acetophenone, 14 parts of 1H,1H,2H,2H-perfluorodecanethiol and 100 parts of dichloromethane in parts by mass. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 4:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:1; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:2; the crosslinking aid is a core-shell structured terpolymer of methyl methacrylate, butadiene and styrene (MBS crosslinking aids PA40 and PA60 of Japan's Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1500; the number average molecular weight of polysiloxane is 10000; the number average molecular weight of polyethylene oxide is 3×10 5 .

[0063] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 500W ultraviolet light for 20 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0064] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0065] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dicarboxylic acid dioctyl ester (DEHCH) and acetyl tributyl citrate (ATBC) are added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0066] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 50℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0067] Example 7

[0068] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 4.5 parts of fluorine-containing POSS, 4 parts of polysiloxane, 5.5 parts of composite heat stabilizer, 7 parts of epoxy soybean oil, 55 parts of cyclohexane 1,2-diethylhexyl dicarboxylate (DEHCH), 2.5 parts of cross-linking aid MBS, 0.9 parts of polyethylene oxide, 3.5 parts of wax powder and 0.4 parts of anionic surfactant.

[0069] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.5 parts of 2,2-dimethoxyphenyl acetophenone, 5 parts of 1H,1H,2H,2H-perfluorodecanethiol and 125 parts of dichloromethane in parts by mass. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 2:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:1; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:2; the crosslinking aid is a terpolymer of methyl methacrylate, butadiene and styrene with a core-shell structure (MBS crosslinking aids PA40 and PA60 of Japan Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1500; the number average molecular weight of polysiloxane is 9000; the number average molecular weight of polyethylene oxide is 3×10 5 .

[0070] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 320W ultraviolet light for 14 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0071] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0072] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir them evenly at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dioctyl dicarboxylate (DEHCH) is added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0073] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 55℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0074] Example 8

[0075] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 5 parts of fluorine-containing POSS, 8 parts of polysiloxane, 8 parts of composite heat stabilizer, 10 parts of epoxy soybean oil, 35 parts of cyclohexane 1,2-diisononyl dicarboxylate (DINCH), 20 parts of acetyl tributyl citrate (ATBC), 5 parts of cross-linking aid MBS, 1.4 parts of polyethylene oxide, 5 parts of wax powder and 0.5 parts of anionic surfactant.

[0076] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.7 parts of 2,2-dimethoxyphenyl acetophenone, 9 parts of 1H,1H,2H,2H-perfluorodecanethiol and 125 parts of dichloromethane in parts by mass. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 3:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:2; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:3; the crosslinking aid is a core-shell structured terpolymer of methyl methacrylate, butadiene and styrene (MBS crosslinking aids PA40 and PA60 of Japan's Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1300; the number average molecular weight of polysiloxane is 11000; the number average molecular weight of polyethylene oxide is 1×10 6 .

[0077] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 350W ultraviolet light for 16 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0078] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0079] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir evenly at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dicarboxylic acid diisononyl ester (DINCH) and acetyl citrate tributyl ester (ATBC) are added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0080] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 45℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0081] Example 9

[0082] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 2 parts of fluorine-containing POSS, 5 parts of polysiloxane, 5.5 parts of composite heat stabilizer, 6 parts of epoxy soybean oil, 35 parts of cyclohexane 1,2-diethylhexyl dicarboxylate (DEHCH), 25 parts of acetyl tributyl citrate (ATBC), 3 parts of cross-linking aid MBS, 1.2 parts of polyethylene oxide, 2 parts of wax powder and 0.2 parts of anionic surfactant.

[0083] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.5 parts of 2,2-dimethoxyphenyl acetophenone, 10 parts of 1H,1H,2H,2H-perfluorodecanethiol and 105 parts of dichloromethane in parts by mass. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 4:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:1; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:3; the crosslinking aid is a terpolymer of methyl methacrylate, butadiene and styrene with a core-shell structure (MBS crosslinking aids PA40 and PA60 of Japan Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1100; the number average molecular weight of polysiloxane is 10000; the number average molecular weight of polyethylene oxide is 2×10 5 .

[0084] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 400W ultraviolet light for 14 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0085] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0086] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir evenly at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dicarboxylic acid diisononyl ester (DINCH) and acetyl citrate tributyl ester (ATBC) are added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0087] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 55℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0088] Example 10

[0089] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 1.5 parts of fluorine-containing POSS, 7 parts of polysiloxane, 7 parts of composite heat stabilizer, 9 parts of epoxy soybean oil, 35 parts of cyclohexane 1,2-diisooctyl dicarboxylate (DEHCH), 30 parts of cyclohexane 1,2-diisononyl dicarboxylate (DINCH), 4 parts of cross-linking aid MBS, 1.3 parts of polyethylene oxide, 2 parts of wax powder and 0.4 parts of anionic surfactant.

[0090] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 1 part of 2,2-dimethoxyphenyl acetophenone, 15 parts of 1H,1H,2H,2H-perfluorodecanethiol and 146 parts of dichloromethane. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 4:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:1; the anionic surfactant is sodium secondary alkyl sulfonate and polystyrene sulfonic acid with a mass ratio of 1:3; the crosslinking aid is a core-shell structured terpolymer of methyl methacrylate, butadiene and styrene (MBS crosslinking aids PA40 and PA60 of Japan's Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1000; the number average molecular weight of polysiloxane is 12000; the number average molecular weight of polyethylene oxide is 1×10 6 .

[0091] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 500W ultraviolet light for 18 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0092] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0093] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dicarboxylic acid diisooctyl ester (DEHCH) and cyclohexane 1,2-dicarboxylic acid diisononyl ester (DINCH) are added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0094] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 50℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0095] Embodiment 11

[0096] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 4 parts of fluorine-containing POSS, 4 parts of polysiloxane, 5 parts of composite thermal stabilizer, 6 parts of epoxy soybean oil, 60 parts of acetyl tributyl citrate (ATBC), 2 parts of cross-linking aid MBS, 0.6 parts of polyethylene oxide, 1 part of wax powder and 0.4 parts of anionic surfactant.

[0097] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.6 parts of 2,2-dimethoxyphenyl acetophenone, 4 parts of 1H,1H,2H,2H-perfluorodecanethiol and 100 parts of dichloromethane in parts by mass. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer with a mass ratio of 2:1, the main stabilizer is stabilizer 1010 and stabilizer 168 with a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax with a mass ratio of 1:2; the anionic surfactant is sodium dodecylbenzene sulfonate and polystyrene sulfonic acid with a mass ratio of 1:2; the crosslinking aid is a core-shell structured terpolymer of methyl methacrylate, butadiene and styrene (MBS crosslinking aids PA40 and PA60 of Japan's Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1200; the number average molecular weight of polysiloxane is 15000; the number average molecular weight of polyethylene oxide is 1×10 6 .

[0098] The fluorine-containing POSS is prepared by the following method: dissolving the high-quality POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 430W ultraviolet light for 11 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0099] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0100] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800rpm to obtain a mixture a; the temperature rises to 45°C, acetyl tributyl citrate (ATBC) is added to the mixture a, and the mixture is continuously stirred at 800-1100rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried to obtain an anti-adhesion and low-temperature resistant material. Among them, the main screw speed is 40-100rmp, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die discharge section is 150-170°C. The material is plasticized by extruder and granulated by air cooling.

[0101] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 45℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0102] Example 12

[0103] The present embodiment provides an anti-adhesion and low-temperature resistant material. The raw materials include, by mass, 100 parts of polyvinyl chloride resin, 4.5 parts of fluorine-containing POSS, 6 parts of polysiloxane, 6 parts of composite heat stabilizer, 8 parts of epoxy soybean oil, 45 parts of cyclohexane 1,2-diisononyl dicarboxylate (DINCH), 2.5 parts of cross-linking aid MBS, 0.7 parts of polyethylene oxide, 3 parts of wax powder and 0.2 parts of anionic surfactant.

[0104] Among them, the raw materials of fluorine-containing POSS include 10 parts of POSS, 0.6 parts of 2,2-dimethoxyphenyl acetophenone, 12 parts of 1H,1H,2H,2H-perfluorodecanethiol and 131 parts of dichloromethane in terms of mass fractions. The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer in a mass ratio of 3:1, the main stabilizer is stabilizer 1010 and stabilizer 168 in a mass ratio of 2:1; the auxiliary stabilizer is phosphite; the wax powder is polyamide wax and maleic anhydride grafted PE wax in a mass ratio of 1:1.5; the anionic surfactant is sodium dodecyl sulfate and polystyrene sulfonic acid in a mass ratio of 1:2; the crosslinking aid is a core-shell structured terpolymer of methyl methacrylate, butadiene and styrene (MBS crosslinking aids PA40 and PA60 of Japan's Kaneka Chemical Industry Co., Ltd.), and the mass ratio of PA40 and PA60 is 2:1. The average degree of polymerization of polyvinyl chloride resin is 1200; the number average molecular weight of polysiloxane is 13000; the number average molecular weight of polyethylene oxide is 7×10 5 .

[0105] The fluorine-containing POSS is prepared by the following method: dissolving the raw material POSS, 2,2-dimethoxyphenylacetophenone and 1H,1H,2H,2H-perfluorodecanethiol in dichloromethane to prepare a solution, and reacting under 380W ultraviolet light for 13 minutes; centrifuging the obtained white precipitate; filtering the white solid precipitate with a negative pressure suction filtration device, washing with dichloromethane, and repeatedly filtering with a negative pressure suction filtration device three times, and vacuum drying the filtered solid powder at 45°C for 6 hours to obtain the fluorine-containing POSS.

[0106] This embodiment also provides a method for preparing the anti-adhesion and low-temperature resistant material, which comprises the following steps:

[0107] According to the above mass parts, weigh polyvinyl chloride resin, fluorine-containing POSS, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant, add them to a high mixer, and mix and stir at a speed of 500-800 rpm to obtain a mixture a; the temperature rises to 45°C, and cyclohexane 1,2-dicarboxylic acid diisooctyl ester (DEHCH) and cyclohexane 1,2-dicarboxylic acid diisononyl ester (DINCH) are added to the mixture a, and the mixture is continuously stirred at 800-1100 rpm and heated to 90°C to obtain a mixture b. When the material is cooled to 30°C, the obtained mixture b is melt-kneaded at 80-170°C using a screw extruder, plasticized, extruded, granulated, dehydrated, air-dried, vibrated and sieved, and air-dried again to obtain an anti-adhesion and low-temperature resistant material. The main engine screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120°C, the temperature of the plasticizing and melting section is 130-150°C, and the temperature of the die head discharge section is 150-170°C. The material is plasticized by the extruder and air-cooled to form granules.

[0108] The anti-adhesion and low-temperature resistant material can be extruded and molded by a pipe extruder to obtain a medical catheter. The temperature of the heating area of ​​the pipe extruder is 145℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 50℃. The inner and outer diameters of the catheter are 6.75mm in outer diameter and 4.5mm in inner diameter.

[0109] Comparative Example 1

[0110] Comparative Example 1 is substantially the same as Example 12, except that 4.5 parts of solid powder A are replaced by 4.5 parts of fluorine-containing POSS in Example 12.

[0111] The solid powder A is prepared by the following method: by weight, 10 parts of POSS, 0.05 parts of 2,2-dimethoxyphenylacetophenone and 2 parts of 1H,1H,2H,2H-perfluorodecanethiol are dissolved in 100 parts of dichloromethane to prepare a solution, and the solution is reacted for 13 minutes under 380W ultraviolet light irradiation; the obtained white precipitate is centrifuged; the white solid precipitate is filtered out by a negative pressure suction filtration device, washed with dichloromethane, and filtered repeatedly by the negative pressure suction filtration device three times, and the filtered solid powder is vacuum dried at 45°C for 6 hours to obtain the solid powder A.

[0112] Comparative Example 2

[0113] Comparative Example 2 is substantially the same as Example 12, except that 4.5 parts of solid powder B are replaced by 4.5 parts of fluorine-containing POSS in Example 12.

[0114] The solid powder B is prepared by the following method: by weight, 10 parts of POSS, 0.26 parts of 2,2-dimethoxyphenylacetophenone and 2 parts of 1H,1H,2H,2H-perfluorodecanethiol are dissolved in 100 parts of dichloromethane to prepare a solution, and the solution is stirred evenly and then reacted under 230W ultraviolet light for 13 minutes; the obtained white precipitate is centrifuged; the white solid precipitate is filtered out by a negative pressure suction filtration device, washed with dichloromethane, and filtered repeatedly by the negative pressure suction filtration device three times, and the filtered solid powder is vacuum dried at 45°C for 6 hours to obtain the solid powder B.

[0115] Comparative Example 3

[0116] Comparative Example 3 is substantially the same as Example 11, except that 4 parts of polysiloxane in Example 11 are removed.

[0117] Comparative Example 4

[0118] Comparative Example 4 is substantially the same as Example 10, except that 4 parts by weight of the crosslinking aid MBS in Example 10 is removed.

[0119] Comparative Example 5

[0120] Comparative Example 5 is substantially the same as Example 9, except that the two parts of wax powder in Example 9 are replaced by two parts of polyethylene wax, which are polyamide wax and maleic anhydride grafted PE wax in a mass ratio of 1:1.

[0121] Comparative Example 6

[0122] Comparative Example 6 is substantially the same as Example 8, except that 0.5 parts of the anionic surfactant in Example 8 is removed.

[0123] Comparative Example 7

[0124] Comparative Example 7 is substantially the same as Example 7, except that 5.5 parts of the composite heat stabilizer in Example 7 is replaced by 5.5 parts by mass of a calcium zinc heat stabilizer.

[0125] Comparative Example 8

[0126] Comparative Example 8 is basically the same as Example 6, except that the anti-adhesion and low-temperature resistant material in Example 6 can be extruded through a pipe extruder to obtain a medical catheter; wherein the temperature of the heating area of ​​the pipe extruder is 145°C to 175°C, the mold temperature is 130°C to 150°C, and the temperature of the cooling water tank is adjusted to 10°C; the inner and outer diameters of the catheter are 6.75 mm in outer diameter and 4.5 mm in inner diameter.

[0127] Comparative Example 9

[0128] A PVC polymer material comprises the following raw materials, measured by mass: 100 parts of polyvinyl chloride resin, 5.5 parts of calcium zinc heat stabilizer, 7 parts of epoxy soybean oil, 3.5 parts of polyethylene wax powder, and 55 parts of cyclohexane 1,2-dioctyl dicarboxylate (DEHCH).

[0129] The PVC polymer material is prepared by the following method:

[0130] The above raw materials are weighed and added into a high mixer, and stirred at a speed of 500-800 rpm to obtain a mixture a; the temperature is raised to 45° C., the speed is controlled to 800-1100 rpm, diisooctyl cyclohexane 1,2-dicarboxylate (DEHCH) is added into the mixture a, the temperature is raised to 90° C. and the stirring is continued to be uniform to obtain a mixture b; the mixture is cooled to 30° C., and the obtained mixture b is melt-kneaded at 80-170° C. by using a screw extruder, plasticized, extruded, and finally granulated; wherein the main screw speed is 40-100 rpm, the temperature of the screw feed section is 80-120° C., the temperature of the plasticizing and melting section is 130-150° C., and the temperature of the die head discharge section is 150-170° C.; after granulation, the PVC polymer material is obtained by dehydration, air drying, vibration screening, and air drying.

[0131] PVC polymer material is extruded by a pipe extruder to obtain a PVC conduit. The heating area temperature of the pipe extruder is 150℃~175℃, the mold temperature is 130℃~150℃, and the cooling water tank temperature is 10℃. The inner and outer diameters of the conduit are set to an outer diameter of 6.75mm and an inner diameter of 4.5mm.

[0132] Comparative Example 10

[0133] Comparative Example 10 is substantially the same as Example 5, except that the polyethylene oxide in Example 5 is removed.

[0134] The above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 1. The performance test methods in the above embodiments and comparative examples are as follows:

[0135] (1) Platelet counting method: Add 0.01 mL of calcium chloride solution and 0.01 mL of low-concentration sodium heparin solution to every 1 mL of blood and mix the three evenly. Place the test sample, negative control, and blank control in a test tube, and add the previously mixed whole blood to each test tube at a ratio of every 12 cm2 of sample to 1 mL of blood. The blank control is blood that has not been in contact with the material. All test tubes are shaken in a water bath at 37°C and 60 rpm for 1 hour. After incubation for 1 hour, add EDTA with a final concentration of 5 mmol / L to each test tube to terminate the reaction, gently mix each test tube, transfer all the blood to another test tube with the same label, and place on ice for later use. After gently rotating and inverting each test tube at least 8 times to mix, place it in a blood analyzer for detection, read the platelet value, and calculate the platelet adhesion rate according to formula (1).

[0136] C=(BA) / B (1)

[0137] A: average platelet count of test samples;

[0138] B: Mean platelet count of blank control.

[0139] The platelet adhesion rate reflects the sample's adhesion to blood cells. The smaller the platelet adhesion rate, the better the sample's anti-blood (cell) adhesion effect.

[0140] (2) Protein adhesion microplate reader method: After washing the sample with phosphate buffer solution (PBS), place it in a 100 μg / ml BSA solution and keep it at a constant temperature of 37°C for 3 hours; take out the soaked sample with tweezers, and then rinse it with PBS buffer solution to wash off the BSA protein that is not adsorbed on the surface; prepare a 0.1% SDS detergent with a mass fraction of PBS buffer solution, measure a certain volume of cleaning solution with a pipette, soak the rinsed sample in the detergent, and ultrasonically clean it for 30 minutes; use a pipette to add the protein solution obtained after cleaning to a 96-well plate, add Bradford reagent, put the 96-well plate into a microplate reader, and measure the absorbance of the solution at an absorption wavelength of 595nm. Finally, calculate the surface adsorption amount based on the standard curve, and measure each sample 3 times to take the average value. The surface adsorption amount reflects the protein adhesion effect. The smaller the surface adsorption amount, the better the anti-protein adhesion effect.

[0141] (3) Fluorescent protein labeling method: After ultraviolet sterilization for 20 minutes, the material was immersed in a 0.5 mg / ml fluorescently labeled bovine serum albumin (BSA-FITC) solution for 2 hours to allow the protein to adsorb on the surface of the material. Then it was gently washed five times with phosphate buffered saline (PBS) to remove protein molecules that were not tightly bound. A confocal laser scanning microscope was used to capture the fluorescent image of the material surface. The fluorescent spots reflect the protein adhesion effect. The fewer the fluorescent spots, the better the anti-protein adhesion effect.

[0142] (4) Contact angle test: Select 5 points on the catheter sample and cut out 2*2cm 2 The sample was tested for water contact angle on the contact angle meter, the water drop volume was set to 8μl / time, and the average value of 5 test points was taken as the sample test result. The contact angle reflects the hydrophilicity of the material. The smaller the contact angle, the better the hydrophilicity of the material.

[0143] (5) Test of UV absorbance of oscillation treatment liquid: Take samples of the same specifications and place them in purified water. Oscillate them in a constant temperature water bath (37°C, 60 rpm) for 7 days. Take the oscillation treatment liquid and measure the absorbance within a certain wavelength range using a 1 cm cuvette with a blank control solution as a reference within 5 hours. The absorbance reflects the precipitation and shedding of the modified sample. The greater the absorbance, the more serious the precipitation and shedding, and the worse the corresponding coating firmness.

[0144] (6) The anti-adhesion and low-temperature resistant material is made into a film, and the tensile properties of the sample are tested according to the GB / T 1040.2-2006 method. The thickness of the test sample is 1 mm.

[0145] (7) The ultraviolet absorbance was tested according to the chemical analysis method in GB / T 14233.1-2008 to determine the precipitation of additives in the test material.

[0146] (8) The determination of cytotoxicity shall be in accordance with the standard: GB / T 16886.5-2017 Biological evaluation of medical devices Part 5: In vitro cytotoxicity test.

[0147] (9) The glass transition temperature shall be determined in accordance with GB / T 19466.2-2004 Plastics Differential Scanning Calorimetry (DSC) Part 2: Determination of glass transition temperature.

[0148] (10) The dynamic friction coefficient is obtained by testing with a friction coefficient tester.

[0149] Table 1 Test results of Examples 1-12 and Comparative Examples 1-10

[0150]

[0151]

[0152]

[0153] Referring to Table 1 and comparing Example 7 with Comparative Example 7, it can be seen that the composite stabilizer used in the present invention has good thermal stability and does not contain metal calcium ions, which greatly weakens the activity of coagulation factor 4 and can avoid the occurrence of coagulation.

[0154] With reference to Table 1 and comparing Example 12 with Comparative Examples 1-2, it can be seen that the present invention introduces fluorine-containing POSS into the PVC material, which greatly reduces the surface energy of the material and reduces the biological cells adhering to the surface. At the same time, since the fluorine-containing POSS is a microscopic cage structure containing a large number of silicon-oxygen bonds, it not only has good biocompatibility, but also can act as a nucleating agent, which is beneficial to the orderly arrangement of PVC molecular chains, making the microscopic molecular chains on the surface of the material more closely arranged, the macroscopic microstructure smoother, and not easy to adsorb proteins, biological tissues and cells.

[0155] With reference to Table 1 and comparing Example 11 with Comparative Example 3, it can be seen that the introduction of polysiloxane in the present invention not only improves the biocompatibility of the material, but also can play a lubricating role in the PVC material. At the same time, since the polysiloxane molecular chain has high flexibility, the low-temperature flexibility of the PVC material is improved, and the interaction between the fluorinated POSS and the various components in the PVC is promoted, so that the fluorinated POSS can be dispersed in the PVC matrix.

[0156] With reference to Table 1 and comparing Example 9 with Comparative Example 5, it can be seen that the addition of polyamide wax and maleic anhydride grafted PE wax in the present invention can not only play a role in processing lubrication, but also reduce the glass transition temperature of the material, improve low temperature resistance, and is an important compatibilizer, further promoting the compatibility of fluorine-containing POSS and other components, and is not easy to precipitate.

[0157] Referring to Table 1 and comparing Example 8 with Comparative Example 6, it can be seen that the addition of anionic surfactants in the present invention makes the surface of the material present a negative charge, which can hinder the adsorption of various negatively charged components (such as hemoglobin, platelets, some plasma proteins, etc.) in the blood environment through electrostatic repulsion, thereby facilitating anti-coagulation.

[0158] Referring to Table 1 and comparing Example 10 with Comparative Example 4, it can be seen that the cross-linking auxiliary agent core-shell structure of methyl methacrylate, butadiene, and styrene terpolymer (MBS) added in the present invention can act as a cross-linking site between molecular chains such as PVC, polysiloxane, plasticizer, and fluorine-containing POSS, promote the compatibility of the components, and improve the low-temperature flexibility and precipitation resistance of the material.

[0159] Referring to Table 1 and comparing Example 6 with Comparative Examples 8-9, it can be seen that in the extrusion molding step of the pipe extruder in the present invention, the temperature of the cooling water tank is a relatively high temperature of 40°C to 60°C, so that the PVC pipe extruded from the die has sufficient time to crystallize, the crystallization is more sufficient and the surface is smoother and flatter. In addition, since the cooling temperature is relatively high and higher than the glass transition temperature, fluorine-containing POSS, polysiloxane and anionic surfactant can be enriched on the surface, further improving the biocompatibility and anti-adhesion effect.

[0160] With reference to Table 1 and by comparing Example 5 with Comparative Example 10, it can be seen that the polyethylene oxide added in the present invention can prevent thrombin from being adsorbed on the surface of the material, further improving the anti-adhesion effect of the material.

[0161] In summary, the present invention uses polyvinyl chloride resin, composite heat stabilizer, plasticizer, epoxy soybean oil, combined with fluorine-containing POSS, modified wax powder, surfactant, polysiloxane, etc., and adopts a preparation process of melt blending granulation and extrusion, and attaches matching process parameters to obtain a low-temperature resistant material with excellent anti-adhesion. The elongation at break at -10°C can reach more than 40%, the elongation at break at 25°C can reach more than 300%, and the glass transition temperature is below -21°C, which can greatly improve the low-temperature flexibility of the material, facilitate the use of medical catheter products, and avoid problems such as poor flexibility or even rupture during use or transportation. At the same time, the water contact angle of the prepared material increases from 85° to 140°, which greatly improves the hydrophobicity of the material, thereby improving the anti-fouling and anti-adhesion effects of the product. The present invention greatly reduces the surface energy of the material and reduces the biological cells adhering to the surface by using the fluorine-containing POSS. At the same time, because the fluorine-containing POSS is a microscopic cage structure containing a large number of silicon-oxygen bonds, it not only has good biocompatibility but also can play a role of a nucleating agent, which is beneficial to the orderly arrangement of PVC molecular chains, makes the arrangement of microscopic molecular chains on the surface of the material more compact, makes the macroscopic and microscopic structures smoother, and is not easy to adsorb proteins, biological tissues and cells.

[0162] In addition, the low temperature resistant and anti-adhesion modification of the present invention is for the modification of PVC pellets, that is, modification from the source, that is, the anti-adhesion material is directly used to prepare the product, which is applicable to a wider range of products and more convenient processing; the preparation process is simple and easy to operate, and the material selection is safe. Only simple reaction, blending, and extrusion devices are required, and more complex production equipment is not required. The preparation process is safe and controllable, and it can also be applied to large-scale production. The present invention has good anti-adhesion stability. The product prepared by the present invention is shaken at 60rpm in a constant temperature water bath at 37°C for 7 days, and still has a significant anti-adhesion effect, and very little precipitation (ultraviolet absorbance of the shaken treatment liquid is less than 0.1Abs), and its anti-adhesion effect lasts longer.

[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. An anti-adhesion and low-temperature resistant material, which comprises, by weight, 100 parts of polyvinyl chloride resin, 1-5 parts of fluorinated octavinyl cage polysilsesquioxane, 3-8 parts of polysiloxane, 5-10 parts of composite heat stabilizer, 5-10 parts of epoxy soybean oil, 30-70 parts of plasticizer, 1-5 parts of crosslinking aid MBS, 0.5-1.5 parts of polyethylene oxide, 0.5-5 parts of wax powder and 0.1-0.5 parts of anionic surfactant.

2. The anti-adhesion and low-temperature resistant material according to claim 1, characterized in that: The raw materials of fluorine-containing octavinyl cage-type polysilsesquioxane include, by weight, 10 parts of cage-type polysilsesquioxane, 2-15 parts of 1H,1H,2H,2H-perfluorodecanethiol, 0.1-1 parts of 2,2-dimethoxyphenylacetophenone and 100-150 parts of dichloromethane; The preparation method of fluorine-containing octavinyl cage-type polysilsesquioxane comprises the following steps: The cage-type polysilsesquioxane, 1H,1H,2H,2H-perfluorodecanethiol and 2,2-dimethoxyphenylacetophenone were dissolved in a dichloromethane solution; the mixture was reacted under 300-500 W ultraviolet light for 10-20 min, and the white precipitate was obtained by centrifugation; the fluorinated octavinyl cage-type polysilsesquioxane was obtained after washing and drying.

3. The anti-adhesion and low-temperature resistant material according to claim 1, characterized in that: The average degree of polymerization of polyvinyl chloride resin is 1000-1800; the number average molecular weight of polysiloxane is 1000-15000; the number average molecular weight of polyethylene oxide is 1×10 5 ~1×10 6 .

4. The anti-adhesion and low-temperature resistant material according to claim 1, characterized in that: The composite heat stabilizer includes a main stabilizer and an auxiliary stabilizer in a mass ratio of (2-4):1, wherein the main stabilizer is stabilizer 1010 and stabilizer 168 in a mass ratio of 2:1; and the auxiliary stabilizer is phosphite.

5. The anti-adhesion and low-temperature resistant material according to claim 1, characterized in that: The plasticizer is one of diisooctyl cyclohexane 1,2-dicarboxylate, diisononyl cyclohexane 1,2-dicarboxylate, and tributyl acetyl citrate, or a combination of at least two of them.

6. The anti-adhesion and low-temperature resistant material according to claim 1, characterized in that: The wax powder is polyamide wax and maleic anhydride grafted PE wax in a mass ratio of 1: (1-2); the anionic surfactant is one of sodium secondary alkyl sulfonate, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate, which are compounded with polystyrene sulfonic acid in a mass ratio of 1: (2-3).

7. A method for preparing the anti-adhesion and low-temperature resistant material according to any one of claims 1 to 6, comprising the following steps: Add polyvinyl chloride resin, fluorinated octavinyl cage polysilsesquioxane, polysiloxane, composite heat stabilizer, epoxy soybean oil, crosslinking aid MBS, wax powder, polyethylene oxide, and anionic surfactant into a high-speed mixer, and stir evenly at 500-800 rpm to obtain a mixture a; Raise the temperature to 40-50°C, add plasticizer to mixture a, continue stirring at 800-1100 rpm and raise the temperature to 80-100°C to obtain mixture b; The mixture is cooled to 20-30°C, melt-kneaded at 80-170°C, plasticized, extruded, and finally granulated to obtain an anti-adhesion and low-temperature resistant material.

8. The preparation method according to claim 7, characterized in that: A single-screw or twin-screw extruder is used for melt kneading at 80-170°C, a screw speed of 40-100 rpm, a screw feed section temperature of 80-120°C, a plasticizing and melting section temperature of 130-150°C, and a die discharge section temperature of 150-170°C.

9. A method for applying the anti-adhesion and low-temperature resistant material according to any one of claims 1 to 6, characterized in that: Anti-adhesion and low-temperature resistant materials are used for continuous renal replacement therapy circuits, extracorporeal membrane oxygenation circuits, extracorporeal circulation circuits, vascular access for dialysis catheters, and vascular access for disposable arteriovenous puncture devices.

10. The application method according to claim 9, characterized in that: The anti-adhesion and low-temperature resistant material is extruded and formed by a pipe extruder; the temperature of the heating area of ​​the pipe extruder is 145°C to 175°C, the temperature of the mold is 130°C to 150°C, and the temperature of the cooling water tank is 40°C to 60°C.

Citation Information

Patent Citations

  • Modified PVC pellet for hemodialysis pipeline

    CN105061928A

  • Medical catheter and preparation method thereof

    CN116061354A

  • Polyvinyl chloride antibacterial composite sheet material

    CN108912527A

  • Anti-adhesion high polymer material and preparation method thereof

    CN115746475A

  • High-temperature-resistant low-temperature-resistant antibacterial PVC (polyvinyl chloride) material and preparation method thereof

    CN117551324A